PERBEDAAN STATUS GIZI PADA ANAK DENGAN PENYAKIT JANTUNG BAWAAN SIANOTIK DAN NON SIANOTIK - Sondakh, Meyrina E.; Kaunang, Erling D.; Rampengan, Novie H. (e-CliniC, 2015)
Abstract: Congenital Heart Disease (CHD) is a disorder that is commonly found. The incidence of CHD in the world is 8-10 among 1,000 births. Although children with mild or moderate CHD usually have normal growth and development, the presence of CHD can result in physical growth retardation. This study aimed to obtain the difference of nutritional status among children with cyanotic and non-cyanotic CHD. This study was a retrospective analytical study with a cross sectional design. This study was conducted at the Child Health Department Prof. Dr. R. D. Kandou Manado. Data of children treated with CHD from 2009-2014 included age, gender, weight, height, and nutritional status. Data were analyzed with Chi-Square test. Of 55 samples, there were 34 boys and 21 girls. The results showed that the most suffered CHD was ventricular septal defect. There were 54.5% of patients with good enough nutrition, 25.5% with malnutrition, and 16.4% with severe malnutrition. The Chi-Square test obtained a P-value of 0.464 (> 0.050) which indicated that there was no difference in nutritional status among children with cyanotic and non-cyanotic CHD. Conclusion: According to the study there was no difference in nutritional status between cyanotic and non-cyanotic congenital heart disease.Keywords:nutritional status, congenital heart disease, cyanotic, non-cyanoticAbstrak: Penyakit Jantung Bawaan (PJB) merupakan kelainan yang cukup banyak ditemukan. Insidensi PJB di dunia 8-10 di antara 1.000 kelahiran. Anak dengan PJB yang tidak begitu parah biasanya memiliki pertumbuhan dan perkembangan yang normal, tetapi adanya PJB dapat mengakibatkan hambatan pertumbuhan jasmani penderita. Penelitian ini bertujuan untuk mengetahui perbedaan status gizi pada anak dengan PJB sianotik dan non sianotik. Penelitian ini menggunakan metode retrospektif analitik dengan desain potong lintang dan dilaksanakan di Bagian Ilmu Kesehatan Anak BLU RSUP Prof. Dr. R. D. Kandou Manado. Data diambil dari semua anak yang dirawat dengan PJB tahun 2009-2014 meliputi umur, jenis kelamin, berat badan, tinggi badan, dan status gizi anak. Analisis data dilakukan dengan uji Chi-Square. Jumlah sampel 55 anak terdiri dari 34 lelaki dan 21 perempuan. Jenis PJB terbanyak yang diderita ialah ventricular septal defect. Penderita dengan gizi cukup 54,5%; gizi kurang 25,5%; dan gizi buruk 16,4%. Dengan uji Chi-Square, didapatkan nilai P 0,464 (< 0,050) yang menunjukkan tidak terdapat perbedaan status gizi antara anak dengan PJB sianotik dan non sianotik. Simpulan: Tidak terdapat perbedaan status gizi antara penyakit jantung bawaan sianotik dan non sianotik.Kata kunci: status gizi, penyakit jantung bawaan, sianotik, nonsianotik